A gold nano-electrode for single ion channel recordings. Issue 8 (12th February 2018) - Okuno, Daichi; Hirano, Minako; Yokota, Hiroaki; Ichinose, Junya; Kira, Takamitsu; Hijiya, Taiki; Uozumi, Chihiro; Yamakami, Masahiro; Ide, Toru
Abstract : A single ion-channel protein on a gold nano-electrode was inserted into an artificial membrane and its current was recorded. Abstract : The artificial bilayer single channel recording technique is commonly used to observe the detailed physiological properties of various ion channel proteins. It permits easy control of the solution and membrane lipid composition, and is also compatible with pharmacological screening devices. However, its use is limited due to low measurement efficiency. Here, we developed a novel artificial bilayer single channel recording technique in which solubilized ion channel proteins immobilized on a gold nano-electrode are directly incorporated into a lipid bilayer at the same time as the bilayer is formed at the tip of it on coming in contact with an aqueous–oil interface. Using this technique, we measured the single channel currents of several types of channels including KcsA, MthK, hBK and P2X4. This technique requires only one action to simultaneously form the bilayers and reconstitute the channels into the membranes. This simplicity greatly increases the measurement efficiency and allows the technique to potentially be combined with high-throughput screening devices.